Exosomes in virus-associated cancer. (1st December 2018) - Wu, Jin'en; Yang, Jing; Ding, Juntao; Guo, Xiaola; Zhu, Xing-Quan; Zheng, Yadong
Abstract: Exosomes are phospholipid bilayer membrane-enclosed vesicles in a size from 30 to 150 nm, carrying a variety of active components, such as proteins, mRNA and miRNAs, and are involved in intercellular communication. Exosomes are released by almost all living cells and detected in various biological fluids. Viruses especially oncogenic viruses have been reported to influence the formation of virus-associated cancer through reshaping the tumor microenvironment via exosomes. In this review, a role of exosomes released by oncogenic virus-infected cells in promoting or inhibiting cancer formation is outlined. Moreover, the prospects and challenges of exosome applications in cancer therapies are critically discussed. Highlights: Oncogenic viruses are responsible for approximately 15% human tumors. Exosomes enhance oncogenic virus infection by transferring oncoproteins and oncogenes. Oncogenic viruses influence the cancer formation though reshaping the tumor microenvironment via exosomes.